THE EFFECT OF THIN CAPITALIZATION, LIQUIDITY AND PROFITABILITY ON TAX AVOIDANCE WITH FINANCIAL DISTRESS AS INTERVENING VARIABLE IN ENERGY SECTOR COMPANIES - Arif Rahman; Agoestina Mappadang (Univesitas Muhammadiyah Tangerang, 2024)
One of the sectors that contributes significantly to the country's revenue is the energy sector. As one of the pillars of the economy, this sector has a significant impact on Gross Domestic Product (GDP). The sizable contribution of the energy sector makes it one of the potential sources of high tax revenue for the state. However, this phenomenon also provides a loophole for tax avoidance practices that can harm state tax revenues. The purpose of this study was to analyze the effect of thin capitalization, profitability and liquidity on tax avoidance with financial distress as an intervening variable. The research population is all energy sector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sampling method in this study used purposive sampling by setting certain criteria according to the researcher's consideration. Data analysis in this study used multiple linear regression using the Eviews statistical program. The results of the study indicate that thin capitalization has a positive and significant effect on financial distress, profitability has a negative and significant effect on financial distress, liquidity has a negative and significant effect on financial distress, thin capitalization has no effect on tax avoidance, profitability has a negative and significant effect on tax avoidance, liquidity has no effect on tax avoidance, financial distress has a positive and significant effect on tax avoidance, financial distress is able to mediate the effect of thin capitalization on tax avoidance, financial distress is able to mediate the effect of profitability on tax avoidance, financial distress is able to mediate the effect of liquidity on tax avoidance.